Viral vector-mediated downregulation of RhoA increases survival and axonal regeneration of retinal ganglion cells - Koch, Jan Christoph; Tönges, Lars; Michel, Uwe; Bähr, Mathias; Lingor, Paul (Frontiers in Cellular Neuroscience, 2014)
The Rho/ROCK pathway is a promising therapeutic target in neurodegenerative and neurotraumatic diseases. Pharmacological inhibition of various pathway members has been shown to promote neuronal regeneration and survival. However, because pharmacological inhibitors are inherently limited in their specificity, shRNA-mediated approaches can add more information on the function of each single kinase involved. Thus, we generated adeno-associated viral vectors (AAV) to specifically downregulate RhoA via shRNA. We found that specific knockdown of RhoA promoted neurite outgrowth of retinal ganglion cells (RGC) grown on the inhibitory substrate CSPG as well as neurite regeneration of primary midbrain neurons after scratch lesion. In the rat optic nerve crush model in vivo, downregulation of RhoA significantly enhanced axonal regeneration compared to control. Moreover, survival of RGCs transduced with AAV expressing RhoA-shRNA was substantially increased at two weeks after optic nerve axotomy. Compared to previous data using pharmacological inhibitors to target RhoA, its upstream regulator Nogo or its main downstream target ROCK2, the specific effects of RhoA downregulation shown here were more pronounced in regard to promoting RGC survival while the stimulatory effects on neurite outgrowth were rather moderate. Taken together, we show here that specific knockdown of RhoA substantially increases neuronal survival after optic nerve axotomy and modestly increases neurite outgrowth in vitro and axonal regeneration after optic nerve crush.